2011
DOI: 10.1373/clinchem.2011.165902
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Tumor Suppressor and Metastasis Suppressor Genes in Circulating Tumor Cells

Abstract: BACKGROUND:Circulating tumor cells (CTCs) are associated with prognosis in a variety of human cancers and have been proposed as a liquid biopsy for follow-up examinations. We show that tumor suppressor and metastasis suppressor genes are epigenetically silenced in CTCs isolated from peripheral blood of breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 40 publications
(53 reference statements)
7
122
0
3
Order By: Relevance
“…For the isolation of CTCs, peripheral blood (20 mL collected in EDTA) was obtained at the midpoint of sample collection by venipuncture as previously described (14 ).…”
Section: Patients and Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…For the isolation of CTCs, peripheral blood (20 mL collected in EDTA) was obtained at the midpoint of sample collection by venipuncture as previously described (14 ).…”
Section: Patients and Samplesmentioning
confidence: 99%
“…CTCs were isolated from 20 mL peripheral blood as previously described (14,20 ). More specifically, after dilution of peripheral blood with 20 mL PBS (pH 7.3), peripheral blood mononuclear cells were obtained by gradient density centrifugation using Ficoll-Paque TM PLUS (GE Healthcare, Bio-Sciences AB) at 670g for 30 min at room temperature.…”
Section: Positive Immunomagnetic Selection Of Ctcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before performing such studies, however, the nature of these circulating EpCAM-positive and CKpositive cells has to be elucidated. Molecular characterization of CTCs can provide valuable information on (a) the expression of cancer-specific genes in these cells (11)(12)(13), (b) mutations in oncogenes or tumor suppressor genes (14 ), (c) epigenetic silencing of tumor suppressor genes and metastasis suppressors (15 ), and (d) fluorescence in situ hybridization-based detection of numerical chromosomal aberrations. As the authors have indicated, false-positive findings may be encountered with the current CTC assays without further molecular analysis of these cells.…”
mentioning
confidence: 99%